Polycaprolactone/maltodextrin nanocarrier for intracellular drug delivery: formulation, uptake mechanism, internalization kinetics, and subcellular localization - Korang-Yeboah M (Dove Medical Press, 2015)
Maxwell Korang-Yeboah,1 Yamini Gorantla,1 Simon A Paulos,1 Pankaj Sharma,2 Jaideep Chaudhary,2 Ravi Palaniappan1 1Department of Pharmaceutical Sciences, College of Pharmacy and Health Sciences, Mercer University, 2Center for Cancer Research and Therapeutic Development (CCRTD), Clark Atlanta University, Atlanta, GA, USA Abstract: Prostate cancer (PCa) disease progression is associated with significant changes in intracellular and extracellular proteins, intracellular signaling mechanism, and cancer cell phenotype. These changes may have direct impact on the cellular interactions with nanocarriers; hence, there is the need for a much-detailed understanding, as nanocarrier cellular internalization and intracellular sorting mechanism correlate directly with bioavailability and clinical efficacy. In this study, we report the differences in the rate and mechanism of cellular internalization of a biocompatible polycaprolactone (PCL)/maltodextrin (MD) nanocarrier system for intracellular drug delivery in LNCaP, PC3, and DU145 PCa cell lines. PCL/MD nanocarriers were designed and characterized. PCL/MD nanocarriers significantly increased the intracellular concentration of coumarin-6 and fluorescein isothiocyanate-labeled bovine serum albumin, a model hydrophobic and large molecule, respectively. Fluorescence microscopy and flow cytometry analysis revealed rapid internalization of the nanocarrier. The extent of nanocarrier cellular internalization correlated directly with cell line aggressiveness. PCL/MD internalization was highest in PC3 followed by DU145 and LNCaP, respectively. Uptake in all PCa cell lines was metabolically dependent. Extraction of endogenous cholesterol by methyl-ß-cyclodextrin reduced uptake by 75%±4.53% in PC3, 64%±6.01% in LNCaP, and 50%±4.50% in DU145, indicating the involvement of endogenous cholesterol in cellular internalization. Internalization of the nanocarrier in LNCaP was mediated mainly by macropinocytosis and clathrin-independent pathways, while internalization in PC3 and DU145 involved clathrin-mediated endocytosis, clathrin-independent pathways, and macropinocytosis. Fluorescence microscopy showed a very diffused and non-compartmentalized subcellular localization of the PCL/MD nanocarriers with possible intranuclear localization and minor colocalization in the lysosomes with time. Keywords: endocytosis, prostate cancer, subcellular targeting, macropinocytosis, clathrin-mediated endocytosis